Concordancia entre los valores de MVO2/kg determinados en condiciones de terreno y laboratorio en boxeadores juveniles - González Revuelta, M. E.; González Marrero, A. Y.; Díaz Gutiérrez, Y.; Gutiérrez, B. (Revista Cubana de medicina del deporte y la cultura fisica, 2020)
Introduction: this is a descriptive, prospective and cross-sectional study of an intentional sample of 10 youth boxers representing the first figures grouped in the light, medium and heavy categories. Objectives: to compare the results obtained for aerobic functional performance (MVO2 / KG) through laboratory and field tests. Methodology: All the boxers were subjected to a strain test in veloergometer as well as a 3000-meter track race test and a modified Peter test, at the beginning and end of the general physical preparation stage of the entrance macrocycle to the National School of Physical Education teachers. Results: It was found that the laboratory test showed the highest values of aerobic power in the two tests performed, while the field tests showed lower values. It was also found that the laboratory test can only be exchanged with the modified Peter Test, although assuming an error range close to the maximum allowed limit. The results are shown in charts and graphs. Conclusions: the test carried out under laboratory conditions threw the highest values for the indicators of the aerobic power during the stage, in the entirety of the boxers being able to this test to be alone interchangeable with modified Peter's test although assuming a range of near error to the allowed maximum limit.